2001
DOI: 10.1002/1521-4141(200112)31:12<3513::aid-immu3513>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Role of CD95-activated caspase-1 processing of IL-1β in TCR-mediated proliferation of HIV-infected CD4+ T cells

Abstract: CD95 plays a critical role in the homeostasis of the immune system, and has been reported to participate in T cell death during HIV infection. Here we report that the response to CD3‐TCR stimulation of CD4+ T cells from HIV‐infected individuals and CD4+ T cells from healthy donors incubated in vitro with HIV‐1Lai depends on the manner the CD3‐TCR complex is engaged. While stimulation by anti‐CD3 antibodies in solution induced CD4 T cell apoptosis both in the absence or presence of anti‐CD95 antibodies, stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 40 publications
2
21
0
2
Order By: Relevance
“…[64][65][66][67] We recently demonstrated that the incubation of resting CD4 þ T cells from healthy donors, even in the presence of an inhibitor of the viral replication, was sufficient to prime CD4 þ T cells for apoptosis in response to CD95 ligation. 68,69 This priming did not require further T-cell activation, suggesting that interactions between the virus and T cells are sufficient. In this study, we found that susceptibility to CD95-induced apoptosis and viral load were higher in SIVmac251-infected macaques that were progressors than in those that were slow progressors, and in animals infected with SIVmac251 than in animals infected with Dnef.…”
Section: Discussionmentioning
confidence: 86%
“…[64][65][66][67] We recently demonstrated that the incubation of resting CD4 þ T cells from healthy donors, even in the presence of an inhibitor of the viral replication, was sufficient to prime CD4 þ T cells for apoptosis in response to CD95 ligation. 68,69 This priming did not require further T-cell activation, suggesting that interactions between the virus and T cells are sufficient. In this study, we found that susceptibility to CD95-induced apoptosis and viral load were higher in SIVmac251-infected macaques that were progressors than in those that were slow progressors, and in animals infected with SIVmac251 than in animals infected with Dnef.…”
Section: Discussionmentioning
confidence: 86%
“…Second, because the sensitivity of cells to death also depends on the degree and duration of immune activation (activation-induced cell death), individual variations may be related to life history and prior infections. Third, individual variations in chemokine receptor expression may determine CD4 ϩ T cell death because the sensitivity of CD4 ϩ T cells to die in vitro depends on the levels and on the nature of the chemokine receptors expressed (34,36,62,63). Herein, we found that a strain of SIV that uses CCR5 and BOB/GPR15 molecules as coreceptors causes death of noncycling primary CD4 ϩ T cells, and that ligation of those coreceptors induced CD4 ϩ T cell death.…”
Section: Cd4mentioning
confidence: 82%
“…A robust increase in CD95 expression has been observed previously in T cells from HIV-1-positive children as compared with healthy controls, as well as increased sensitivity to CD95-mediated cell death (29). Therefore, we measured CD95 expression on CD4 ϩ and CD8 ϩ T cells by triple FACS staining.…”
Section: Cd95 Expression Is Correlated To Disease Status and Agementioning
confidence: 87%